REMEDIASI MISKONSEPSI SISWA DALAM MATERI SUDUT ISTIMEWA MELALUI WAWANCARA KLINIS BERBANTUAN GEOGEBRA - Iqlima, Nurmaya; Sugiatno, Sugiatno; Mirza, Ade (Universitas Tanjungpura, 2025)
The phenomenon of misconceptions in special angle trigonometry learning constitutes a significant impediment affecting mathematical understanding construction among students. This research aims to analyze remediation strategy implementation through clinical interview approaches integrated with GeoGebra technology to overcome conceptual distortions within trigonometric domains. Qualitative methodology with case study design was applied to three Grade XI subjects from SMAS Muhammadiyah 1 Pontianak who were identified experiencing dominant misconceptions based on diagnostic assessment outcomes. Data collection techniques involved instrument triangulation through diagnostic pre-testing, clinical interview implementation assisted by GeoGebra visualization, and post-intervention evaluation. Data analysis employed Miles-Huberman framework with reduction, display, and finding verification procedures. Investigation results identified three systematic misconception categories: procedural memorization-based computational distortions, inadequate conceptual generalizations, and erroneous specialization interpretations of trigonometric values. Remedial intervention demonstrated substantial effectiveness with misconception elimination rates reaching 89% for two subjects, while the third subject retained one residual misconception aspect. GeoGebra's dynamic visualization facilitated understanding reconstruction through interactive geometric representations that activated multiple modalities of cognitive processing. These findings confirm that integrating clinical interviews with adaptive learning technology produces paradigmatic transformation from rote learning toward sustainable and transferable conceptual understanding construction in trigonometric contexts. The research contributes innovative pedagogical frameworks for mathematical misconception remediation through technology-enhanced diagnostic approaches.